2011
DOI: 10.1080/16506073.2010.550058
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Telehealth Treatments for Posttraumatic Stress-Related Symptoms: A Meta-Analysis

Abstract: This meta-analysis summarizes the findings of outcome research on the degree to which telehealth treatments reduce posttraumatic stress disorder (PTSD)-related symptoms. In a search of the literature, 13 studies were identified for inclusion in the meta-analysis and were coded for relevant variables. A total of 725 participants were included. Results indicate that telehealth treatments are associated with significant pre- to postreduction in PTSD symptoms (d = 0.99, 95% confidence interval [CI]: 0.87-1.11, p <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
65
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 37 publications
9
65
1
4
Order By: Relevance
“…Despite the above concerns about online counseling, a growing number of researchers have found evidence supporting the effectiveness of online counseling for a variety of psychological problems, including depression, panic disorder, social anxiety, post-traumatic stress disorder, and eating disorders (Sloan et al 2011). In addition, several studies about client satisfaction with online counseling have revealed encouraging results.…”
Section: Online Versus F2f Counselingmentioning
confidence: 98%
“…Despite the above concerns about online counseling, a growing number of researchers have found evidence supporting the effectiveness of online counseling for a variety of psychological problems, including depression, panic disorder, social anxiety, post-traumatic stress disorder, and eating disorders (Sloan et al 2011). In addition, several studies about client satisfaction with online counseling have revealed encouraging results.…”
Section: Online Versus F2f Counselingmentioning
confidence: 98%
“…With the continuing leadership of Dr. Antonette Zeiss (Zeiss & Karlin, 2011), many initiatives have been launched over the past several years to meet the goals of VA's 2004 MHSP. suggested the adaptation of technology to deliver psychotherapy; the VA has recognized that telehealth technologies (e.g., web-based, phone, video teleconference) are an increasingly important method of ensuring equal and timely access to mental health care services to patients who would otherwise not have such access to services because they live in locations that are a considerable distance from the nearest VA facility (Sloan, Gallagher, Feinstein, Lee, & Pruneau, 2011). Another advantage of telehealth technology is its ability to provide mental healthcare services quickly and efficiently to large numbers of individuals.…”
Section: Declaration Of Conflicting Interestsmentioning
confidence: 99%
“…Based on AMSTAR assessment of the seven meta-analyses, one was rated high, 32 five were rated moderate, 16,25,[33][34][35] and one was rated low. 36 Of the 20 systematic reviews, two were rated high, 20,37 ten were rated moderate, 17,18,28,30,[38][39][40][41][42][43] and eight were rated low.…”
Section: The Clinical Evidence Basementioning
confidence: 99%